Suberin: the biopolyester at the frontier of plants - Graça, José (Frontiers in Chemistry, 2015)
Suberin is a lipophilic macromolecule found in specialized plant cell walls, wherever insulation or protection towards the surroundings is needed. Suberized cells form the periderm, the tissue that envelops secondary stems as part of the bark, and develop as the sealing tissue after wounding or leaf abscission. Suberin is a complex polyester built from poly-functional long-chain fatty acids (suberin acids) and glycerol. The suberin acids composition of a number of plant tissues and species is now established, but how the polyester macromolecule is assembled within the suberized cell walls is not known. In the last years contributions from several areas have however significantly enriched our understanding of suberin. The primary structure of the polyester, i.e. how the suberin acids and glycerol are sequentially linked was revealed, together with the stereochemistry of the mid-chain functional groups some suberin acids have; solid-state NMR studies showed the presence of methylene chains spatially separated and with different molecular mobility; biophysical studies showed the membrane behaviour of suberin acids derivatives, allowing new insights on structure-properties relationships; and a number of candidate genes were conclusively related to suberin biosynthesis. The comprehension of suberin as a macromolecule will be essential to understand its vital protective roles in plants and how they will deal with eventual environmental changes. Suberin is also expected to be a source for high-performing bio-based chemicals, taking advantage of the structural uniqueness of their constituent suberin acids.